EFL/ESL Students' Perceptions of Distributive, Procedural, and Interactional Justice: The Impact of Positive Teacher-Student Relation - Yang, Dan (Frontiers in Psychology, 2021)
The correlation between teacher-student interpersonal relationships and students’ perception of different dimensions of justice using in the learning context has been found absolutely important since it can provide a nice learning environment for students in which they can comfortably learn a new language. Even though several studies have been carried out regarding the above-mentioned points, a review paper that focuses on the importance between these two variables by which students’ learning is influenced seems of great interest. In this study, the author has strived hard to highlight the interplay between the aforementioned variables. First of all, Justice and its dimensions including distributive, procedural, and interactional justice are described in the learning context. Then the effect of the positive relationship between teachers and students is accentuated. Following it, different types of characteristics that are crucially noticeable considering teacher-student interpersonal relationship including “teachers care”, “teacher clarity”, “teacher confirmation”, “teacher credibility”, “teacher immediacy”, “teacher stroke”, “teacher-student rapport” are discussed. The term “positive psychology” accompanied by its factors is defined then. What is discussed then is classroom justice as a teacher-student interpersonal factor. Finally, it is concluded with implications and suggestions for future studies.